The functional connectivity of the middle frontal cortex predicts ketamine’s outcome in major depressive disorder - Zhang, Fan; Wang, Chengyu; Lan, Xiaofeng; Li, Weicheng; Fu, Ling; Ye, Yanxiang; Liu, Haiyan; Wu, Kai; Zhou, Yanling; Ning, Yuping (Frontiers in Neuroscience, 2022)
Background: Researchers have explored the mechanisms of ketamine in patients with major depressive disorder(MDD) through MRI for its robust anti-depressive effect. Notably, many results are limited in previously selected brain regions and consistently heterogeneous, particularly in the functional connectivity analysis. Here, we used the significantly different results in degree centrality (DC) analysis as seeds to explore the functional connectivity changes in MDD patients to identify an imaging biomarker of ketamine’s effect. Methods: Forty-four MDD patients aged 18 to 65 received six intravenous ketamine over 12 days. Depressive symptoms were estimated and MRI scans were performed at baseline and the day after the sixth infusion. Forty-five MRI scans from health controls (HCs) were also included in the analysis. Result: Compare with the nonresponders, the responders have significantly decreased DC values in the right Middle Frontal Gyrus(MFG). The zFC values showed a significant difference in the region of the right Supplementary Motor Area (SMA), which also overlaps the bilateral median cingulum gyrus among responders, nonresponders, and HCs. In the posthoc analysis, responders have higher zFC values than nonresponders and HCs, and nonresponders are lower than HCs. Importantly, the zFC values between MFG and SMA(overlaps bilateral median cingulum gyrus) show collection with ΔMADRS%, and the zFC values of this region could be an imaging biomarker to predict the ketamine reaction in the Receiver operating characteristic （ROC） curve analysis. Conclusion: Our results revealed the FC between DMN and SMA&mACC was higher correlated with depressive symptoms and has the potential to be a neuroimaging biomarker to predict ketamine reaction.